Partial normalization of microbiota dysbiosis in condyloma acuminatum patients following treatment - Chen, Kai; Li, Meng; Fu, Tian-Qi; Hu, Yan-Yan; Chen, Lan; Huang, Qian; Xu, Li; Zeng, Zhi-Liang; Li, Dong-Sheng (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCondyloma acuminatum (CA) is the most common sexually transmitted disease and the presence of microbiota dysbiosis has been observed to promote the progress of the disease. However, the explicit characteristics of microbiota dysbiosis in CA patients have not been well elucidated yet.MethodsWe recruited 40 CA patients who received QYXJ (an in-hospital prescription that has been used to treat CA for many years) treatment and 40 healthy controls (HC) in the current study. Before and after two weeks QYXJ administration, the skin microbiome of each patient was assessed using 16S rRNA gene sequencing. ResultsHere, we found increased relative abundances of Staphylococcus and Lactobacillus, whereas a decreased Escherichia in CA patients relative to healthy controls (HC). Moreover, we also observed significant alpha and beta diversity differences between the CA and HC groups, and QYXJ treatment effectivity attenuated these alterations of genus level and microbial diversity in patients with CA. Importantly, further microbial interaction and function analyses revealed the significantly enriched relative abundance of Caldivirga and Streptococcus in microbial community, decreased complexity of microbial interactions and downregulated metabolic pathways in CA patients, including membrane transport, lipid metabolism and carbohydrate metabolism. Remarkably, QYXJ administration partially restored these microbiota dysbiosis, which subsequently shifts microbiomes of patients with CA towards healthy-like microbiota. ConclusionThis study further confirmed the changes of skin microbiome in CA pathogenesis and firstly revealed the protective effects of QYXJ in microbiota dysbiosis resolution, suggesting its potential role as a novel method for CA treatment.